Analysis and investigation of ballistic impact on ceramic/metal composite armour - Gonçalves, D.P.; de Melo, F.C.L.; Klein, A.N.; Al-Qureshi, H.A. (International journal of machine tools & manufacture, 2004)
The subject of this paper is to analyze the impact of projectiles against ceramic/metal armour using a simple one-dimensional mode. The model allows the calculation of the loss of projectile mass and its velocity, and gives the deflection of the backup material. This work also investigates the influence of grain size of the ceramic material on ballistic performance, which is very useful during selection of the best material for each application. Therefore, two formulations of the same ceramic material were produced. They had the same chemical composition, the same mechanical properties, but different grain size. The ballistic performances were compared measuring the maximum velocity each formulation was able to support, without perforation.